Chasing the light : writing, directing, and surviving Platoon, Midnight Express, Scarface, Salvador, and the movie game - Stone, Oliver (Houghton Mifflin Harcourt, 2020)
"An intimate memoir by the controversial, Oscar-winning director and screenwriter about his privileged New York upbringing, volunteering for combat, and his struggles and triumphs making such landmark films as Platoon, Midnight Express, and Scarface"--